Design strategy for flying capacitor multilevel converter based on PSC-PWM - Hema, S; Sharmila, N; Selvi, S; Krishnaveni, M (International Journal of Engineering and Technology, 2018)
This paper presents flying capacitor multilevel converters. This is the new multilevel topology with the concept of phase-shifted carrier pulse width modulation which will generate the signals. This signal will generate by using phase-shift carrier with modulating signal. The execution of proposed structure of this technique is shown with the help of waveforms. The advantages of this proposed topology is shown in the simulation. All possible switching states are explained in the modulation strategy. The different performance of proposed topology is compared with other flying capacitor multilevel structures. Simulation result for all the switching states are explained with respective waveforms. Proposed topology is superior to the other flying capacitor multilevel structure from different standpoints. And mainly, it reduces the number of high frequency switches, the number of flying capacitor and at the same time it improves the quality of output voltage. The experimental setup is used to validate the modulation strategy and other theoretical findings.Â Â